Effect of potassium and stress mitigating chemicals on growth and yield of chickpea (Cicer arietinum L.) - Manjeet Dhaka; Devi Lal Dhaker; O. P. Sharma; Pradeep Dhaka (Annals of Agricultural Research, 2024)
A field study on “Effect of Potassium and Stress Mitigating Chemicals on Growth and Yield of Chickpea (Cicer arietinum L.)” was conducted at Research Farm, School of Agriculture, Suresh Gyan Vihar University, Jaipur during rabi season of 2022-23. The experimentalresults showed that the growth and yield of chickpeawere significantly increased due to application of potassium and stress mitigating chemical. The maximum plant height, dry matter accumulation, number of branches plant-1, number of pods plant-1, num ber of seeds pod-1, seed yield, straw yield and biological yieldof chickpea was obtained with the application of potassium @ 20 kg ha-1 which was significantly superior as compared to control and application of potas sium @ 10 kg ha-1.Results further showed that foliar spray of thiourea @ 500 ppm or thioglycolic acid @ 100 ppm recorded highest plant height, dry matter accumulation, number of branches plant-1, number of pods plant-1, number of seeds pod-1, seed yield, straw yield and biological yield of chickpea.